DIFFERENCES IN PSYCHOLOGICAL CHARACTERISTICS OF ELITE JUNIOR HANDBALL PLAYERS - KŐNIG-GÖRÖGH, Dóra; ÖKRÖS, Csaba; GYÖMBÉR, Noémi (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2019)
The aim of the present paper is to investigate personality traits among junior handball players in different player positions and examine whether a standard can be established as to what personality traits the players in the individual positions should have. A Big Five Questionnaire survey was conducted in the early training period of 2016-2017 among elite Hungarian junior handball players (n=164, in terms of posts of playing players 25% were backcourt players, 23.2% wingers and 18.9% playmakers.). Big Five personality traits: Extroversion, Agreeableness, Conscientiousness, Neuroticism and Openness. Neuroticism showed significant differences by gender (t=3.9 p<0.001), where males reached significantly higher scores (Mmale=65.7, Mfemale=53.1). 16, 17 and 18 year-old players reported higher levels in each personality trait than 14-15 year olds (p<0.001). Playing posts did not indicate any significant differences. All personality traits showed significant and strong interrelations. Only Neuroticism resulted in significant interaction of gender and age (p<.05). The results of investigating personality profile characteristics by gender, age and posts have revealed crucial factors of handball players. It is important to underline that a sport psychological approach, dealing with personality profiles, has significant benefits in the development of players, particularly adolescent players.